Characterisation of a mouse model of chronic cerebral hypoperfusion and its application to investigating the impact of hypoperfusion on the development of Alzheimer’s disease - Coltman, Robin Bruce (The University of Edinburgh, 2012)
The integrity of brain white matter is vital for the interneuronal signalling between distinct brain regions required for normal cognitive function. White matter integrity is compromised with ageing and could contribute to age-related cognitive decline. Chronic cerebral hypoperfusion is thought to underlie the development of white matter pathology and cognitive changes, often seen in the elderly. Additionally, the development of regional hypoperfusion and white matter damage are thought to be early events in Alzheimer’s disease (AD) pathogenesis. This thesis set out to test the hypothesis that chronic cerebral hypoperfusion underlies the development of white matter pathology and cognitive decline and also that chronic cerebral hypoperfusion causes the development of Ab pathology in AD. The first aim was to investigate the impact of hypoperfusion on the development of white matter damage and different aspects of cognition in a mouse model of chronic cerebral hypoperfusion. Two studies were undertaken to address this. The first study examined the temporal development of pathology following hypoperfusion induced by bilateral carotid artery stenosis (BCAS) using microcoils Hypoperfusion was induced in wild type (WT) mice and the pathological changes examined at one week, two weeks, one month and two months. Hypoperfused animals developed a diffuse and widespread white matter pathology, present from one week, which occurred predominantly in the myelin component of white matter; this was accompanied by minimal axonal damage. A second study examined the impact of hypoperfusion on different aspects of spatial memory and further investigated pathological changes in the model at one and two months. Behavioural testing revealed a significant impairment in spatial working memory but not episodic memory or spatial reference memory in hypoperfused animals. In the same mice, pathological assessment indicated that there was a significant increase in levels of myelin damage and elevated levels of microglial activation as compared to shams. These results demonstrate that modest reductions in cerebral blood flow are sufficient to cause the development of white matter damage and the development of cognitive deficits. The second aim was to investigate the impact of hypoperfusion on the development of white matter and amyloid pathology in a mouse model (3xTg-AD) of AD. To address this, using 2 different sizes of microcoils (0.18mm and 0.16mm internal diameter) BCAS of varying severities was induced in 3xTg-AD mice and white matter and Ab pathology were assessed at one month. Circle of Willis (CoW) architecture was also compared between WT and 3xTg-AD mice. Overall white matter pathology was not exacerbated in experimental 3xTg-AD mice with BCAS induced by 0.18mm coils. However with a greater level of stenosis (0.16mm coil) ischaemic damage to neuronal perikarya was present in most experimental animals. In addition to ischaemic damage, localised areas of severe white matter pathology were also observed in conjunction with subtle changes to white matter Ab levels. Hypoperfusion did not impact on the development of intraneuronal Ab pathology, other than in the presence of ischaemic damage when levels were reduced. Comparison of CoW architecture between WT and 3xTg-AD mice revealed strain specific differences in the presence and morphology of the posterior communicating artery which may explain the lack of pathology in 3xTg-AD mice as compared to WT following BCAS induced using 0.18mm dia. microcoils. The third aim was to investigate whether white matter protein composition changed with age and also whether ageing conferred increased vulnerability to hypoperfusion. To address this, white matter protein levels were compared between young (3-4 months) and old (12-13 months) 3xTg-AD mice. White matter pathology was compared between sham and hypoperfused animals in the aged cohort. Levels of myelin basic protein and 2', 3'-cyclic nucleotide 3'- phosphodiesterase were found to be significantly increased whilst levels of myelin associated glycoprotein were significantly reduced with ageing. These results suggest that changes in myelin protein composition may contribute to the development of age related white matter pathology. White matter pathology was not exacerbated in aged hypoperfused animals following one month of hypoperfusion as compared to shams. The results presented within the thesis demonstrate that chronic cerebral hypoperfusion precipitates the development of selective white matter damage and impacts on cognition. Also it has been shown that where hypoperfusion is severe enough to cause ischaemic damage to neuronal perikarya and localised areas of severe white matter pathology, alterations in white matter Ab levels can occur. Hypoperfusion does not impact on APP processing or on intraneuronal levels of APP or Ab, other than in the presence of ischaemic damage to neuronal perikarya, when levels are reduced. These findings highlight the importance of early intervention strategies in the treatment of vascular risk factors which can lead to hypoperfusion and the development of white matter damage and a decline in cognitive function in later life. These findings also suggest that repair or prevention of white matter damage may be an appropriate strategy for the attenuation of cognitive decline following onset of hypoperfusion. This thesis also highlights some of the limitations of animal models of human disease.
Keywords: hypoperfusion; white matter; cognition; Alzheimer’s disease; mild cognitive impairment